“Under Erasure”: Suppressed and Trans-Ethnic Māori Identities - Stewart, GT; Stewart-Harawira, M (The Trustees of Indiana University, 2020)
The questions raised by Māori identity are not static, but complex and changing over time. The ethnicity known as “Māori” came into existence in colonial New Zealand as a new, pan-tribal identity concept, in response to the trauma of invasion and dispossession by large numbers of mainly British settlers. Ideas of Māori identity have changed over the course of succeeding generations in response to wider social and economic changes. While inter-ethnic marriages and other sexual liaisons have been common throughout the Māori-Pākehā relationship, the nature of such unions, and the identity choices available to their descendants, have varied according to era and social locus. In colonial families, the memory of a Māori ancestor was often deliberately suppressed, and children were encouraged to deny that part of their history and “become” European New Zealanders: a classic form of what we call “trans-ethnicity.” From a Māori perspective, the relationship with Pākehā has been marked by a series of losses: loss of land, language, social cohesion, even loss of knowledge of whakapapa (genealogy). This article explores this last form of loss, which leads to “suppressed” Māori identities, and possible effects of attempting to recover such lost Māori identity rights.
Keywords: Ethnicity; Māori; Pākehā; Suppressed identity; Trans-ethnicity; Whakapapa